Integration of the Video Response App FlipGrid in the Business Writing Classroom - McLain, Terrill Reid (International Journal of Educational Technology and Learning, 2018)
In business English writing classes, second language learners can be reticent to speak about their writings. To combat this and give students more opportunities to practice speaking and allow instructors the ability to measure the engagement, a video capture tool is needed that will enable students to have conversations asynchronously and produce the language vocally outside of class. Recently a tool was developed where speaking tasks can be created using a video response service called FlipGrid. This web-based educational technology tool gives instructors the means to help students increase their productive language skills by increasing the time students spend speaking outside class, with the added accountability of video. Both spontaneous and planned vocal practice assignments can be created with this tool resulting in more student engagement and speaking practice. This paper discusses the need and rationale for using the service and shares the results of a class evaluation after implementing the video capture tool in a business writing class. The assessment discovered that students found the tool easy to use and noticed increases with both their perceived time speaking English between classes and their perceived English-speaking confidence.